1997
DOI: 10.1099/00221287-143-4-1133
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux response to salt-induced stress in the halotoleirant yeast Debaryomyces hansenii

Abstract: The toxic effect of NaCl and KCI on growth of the marine yeast Debaryomyces hansenii on glucose or glycerol was studied. Above a threshold value, both salts reduced the specific growth rate, specific glucose and glycerol respiration rates and specific glucose fermentation rate, as well as biomass yields. The exponential inhibition constant, k, and minimum toxic concentration, cmin, were similar for all physiological parameters assayed. The effect of either salt on the specific activity of several glycolytic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
2
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 14 publications
10
48
2
1
Order By: Relevance
“…hansenii (Neves et al, 1997). However, the level of resistance of any strain may also be temperature dependent (Trollmo et al, 1988 ;Prista & MadeiraLopes, 1995 ;Tokuoka, 1993) or pH dependent (Tokuoka, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…hansenii (Neves et al, 1997). However, the level of resistance of any strain may also be temperature dependent (Trollmo et al, 1988 ;Prista & MadeiraLopes, 1995 ;Tokuoka, 1993) or pH dependent (Tokuoka, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 years ago, it was reported that among several marine yeasts, D. hansenii was the least affected by high concentrations of NaCl (21,27). D. hansenii accumulates high amounts of Na ϩ , and in this yeast, Na ϩ is not more toxic than K ϩ (18,24,30). More recently it was shown that Na ϩ improves the performance of D. hansenii under different stress conditions (1).…”
Section: Two Genes Encoding Namentioning
confidence: 99%
“…The difference is not easily explainable. Other authors have used different media, in which the basal concentration of K + was lower, approximately 10 m by Norkrans (1966), and by Neves et al (1997). The main difference was that, instead of a mineral-defined medium, we used YPD medium without any addition, containing approximately 15 m of KCl.…”
Section: Transport Properties and Possible Mechanismsmentioning
confidence: 96%
“…At moderate concentrations of this salt, it can grow and carry out the main functions such as respiration and fermentation (Neves et al, 1997). Hobot and Jennings (1981) and Prista et al (1997) also observed that this yeast grows moderately better in the presence of moderate concentrations of NaCl.…”
Section: Introductionmentioning
confidence: 93%